WAYANG DAN MUTASI VALUE OF ISLAM DALAM PERMAINAN WAYANG - Imron, Ahmad Fauzi (Humanistika : Jurnal Keislaman, 2016)
Abstract: Islam is a religion rahmatan lil Alamin (blessing for the universe), of course, we as Muslims are required to make Islam as guidance in social life, because sometimes the habits or norms terben tuk in society are not in accordance with the teachings of Islam we already believe to be true. For that it is necessary the straightening straightening mengkiblat in the teachings of Islam, which indeed it is an absolute thing to do as a Muslim, which of course it can not be separated from the translation of translation as a form of extracting the values of Islam to understand. The rest leave in case there is need for appropriate methods as the approach used in the hang of the moral values of Islam to the community.In this study the researchers wanted to know the purpose of establishing a puppet in the hamlet syadat Gentong as media approach to disseminate the teachings of Islam and the effectiveness of the puppet syadat in transforming the teachings of Islam to the people hamlet Gentong. This research was conducted in the hamlet Gentong-Purwoasri Singosari Malang.In collecting these data the researchers used the method of observation, interviews, documentaries, questionnaires, and analyze the data in percentages. Population taken in peneletian is the whole society Gentong hamlet of 200 people, while researchers only take 40 people (20%) to be sampled comprised of community leaders, the village, the elderly and youth.From the results of this study can be obtained from the data that the purpose of the puppet Syadat is to disseminate the teachings of Islam and on the transformation of moral values of Islam through a puppet show Syadat dikatan be very effective. Because this approach is in accordance with the background of village communities Gentong which largely favor the arts that smelled gamelan.Â Keywords: Values of Islam, transformation, puppet shows syadat